The effect of conspecific density on emergence of Lestes bipupillatus calvert, 1909 (Odonata: Lestidae) - Leite, Ricardo Cardoso [UNESP]; Vilardi, Gabriel Cestari; Guillermo-Ferreira, Rhainer [UNESP]; Bispo, Pitágoras da Conceição [UNESP] (Hindawi, 2014)
Conspecific density may influence adult recruitment and consequently population dynamics. Several studies have shown the density dependence of larvae growth rates in Odonata. However, few studies studied how conspecific density influence final instar larvae emergence date decisions. Considering that larvae may choose the date of emergence, the present study investigated if density affects larvae choice. For this, we reared eight final instar larvae in individual aquaria and other 24 larvae in aquaria with three larvae each. This way, we simulated environments with low and high larval densities. We then noted the days that larvae took to emerge and compared it between low and high density groups. The results showed that larvae seem to emerge earlier when in high densities (Mann-Whitney, U = 10.000, P = 0.03). These results support the hypothesis that damselfly last instar larvae may postpone or hasten emergence in response to the social environment and related constraints.